Interactive effect of anthropogenic activities and seasonal changes on the biophysicochemical properties and heavy metal status of tropical surface water resources - Albert Banunle; Alex Amerh Agbeshie; Mary Queenette Odumanye; Rita Adjei; Appiah Bosomtwi (Scientific African)
Seasonal changes and uncontrolled anthropogenic activities alter surface water resources quality and threaten access to water for consumptive and non-consumptive needs of humankind. This study examines the interactive impact of seasonal variation and anthropogenic activities on selected biophysicochemical properties and heavy metal status of tropical surface water resources. The study was conducted with water samples taken from upstream, midstream and downstream of the networked surface water system of the Barekese and Owabi dams in the Ashanti Region of Ghana during the wet season (March – Mid. October 2019) and dry season (Mid. October – February,2019). The result revealed that the downstream had significantly higher levels of conductivity, BOD, NO3-N, NH4-N , as well as Escherichia coli (E. coli) when compared to the midstream and upstream. The levels of NO3-N were significantly higher during the wet season while conductivity, TSS, E. coli and copper were higher during the dry season. Significant interactive effects between seasons and anthropogenic activities on water quality were observed. The anthropogenic impacts on conductivity, E. coli, and copper concentration were observed during the dry season while that of NO3-N was observed during the wet season. Overall, the water quality was poorest during the dry season and mainly in the downstream where anthropogenic activities are pronounced. This means that efforts towards improving surface water quality should be targeted at downstream activities, especially during the dry season. The study recommends the need for effective monitoring and control of activities such as dry season farming and indiscriminate discharge of waste into tributaries of surface water especially within the downstream.